'Disappearing workers': Foxconn in Europe and the changing role of temporary work agencies. (February 2017) - Andrijasevic, Rutvica; Sacchetto, Devi
This article investigates the role of temporary work agencies (TWAs) at Foxconn's assembly plants in the Czech Republic. Drawing on ethnographic fieldwork, it shows TWAs' comprehensive management of migrant labour: recruitment and selection in the countries of origin; cross-border transportation, work and living arrangements in the country of destination; and return to the countries of origin during periods of low production. The article asks whether the distinctiveness of this specific mode of labour management can be understood adequately within the framework of existing theories on the temporary staffing industry. In approaching the staffing industry through the lens of migration labour analysis, the article reveals two key findings. Firstly, TWAs are creating new labour markets but do so by eroding workers' rights and enabling new modalities of exploitation. Secondly, the diversification of TWAs' roles and operations has transformed TWAs from intermediaries between capital and labour to enterprises in their own right.